Metacognition during unfamiliar face matching. (4th January 2022) - Kramer, Robin S. S.; Gous, Georgina; Mireku, Michael O.; Ward, Robert
Abstract: Kruger and Dunning (1999) described a metacognitive bias in which insight into performance is linked to competence: poorer performers are less aware of their mistakes than better performers. Competence‐based insight has been argued to apply generally across task domains, including a recent report investigating social cognition using a variety of face‐matching tasks. Problematically, serious statistical and methodological criticisms have been directed against the traditional method of analysis used by researchers in this field. Here, we further illustrate these issues and investigate new sources of insight within unfamiliar face matching. Over two experiments (total N  = 1077), where Experiment 2 was a preregistered replication of the key findings from Experiment 1, we found that insight into performance was multi‐faceted. Participants demonstrated insight which was not based on competence, in the form of accurate updating of estimated performance. We also found evidence of insight which was based on competence: the difference in confidence on correct versus incorrect trials increased with competence. By providing ways that we can move beyond problematic, traditional approaches, we have begun to reveal a more realistic story regarding the nature of insight into face perception.